Creating an industry-level business model for sustainability: The case of the European ports industry. (10th September 2018) - Langenus, Mychal; Dooms, Michaël
Abstract: The seaports industry is an industry that produces voluminous negative externalities on the local and regional level, and is also affected by the challenges of climate change. To improve the dimensions of the sustainability – economic, social or ecological dimensions for cleaner production - on an industry level, there is a need to build an inter-organizational network. In this paper, we apply a virtual learning model for the setup of an interorganizational network (ION) for sustainable development in the ports industry, which offers a unique context of high stakeholder complexity and conflict. The value of this paper is that it builds on previous research on the role of the net broker function for triple bottom line transitions through an action research project for the creation of an ION for sustainable development. We furthermore provide managerial recommendations for the setup of such networks.